Paid Subscriptions and Premium Content: Online News Publishers’ Monetisation Strategies - Mathiasová, Alexandra; Solík, Martin; Mináriková, Juliána (Communication Today, 2022)
Online journalism is characterised by specific features that distinguish it from its predecessors. It is not only interactivity, timeliness and new elements that make it unique. The way in which digital media are funded is also interesting. While in print media it is customary to pay directly for a copy of a newspaper, the situation is different in the online space. News content is usually freely accessible and online advertising in the form of banner ads or PR pieces is present. However, funding the medium can be unprofitable in this model, which is why some publishers have chosen to hide their web content behind a paywall. Recipients must thus pay for news directly again – in the form of subscriptions. The aim of the study is to shed light on the issue of online media financing in order to explore different monetisation strategies and their efficiency in the era of COVID-19.